Aslamic Religious Intertextuality among Some of Apollo Poets (Journal of Hama University, 2019)
This paper examines poetic discourse in the poetry of the Apollo Group. It aims at uncovering some of the creative tendencies in that poetry, and at highlighting some of those religious inclinations that uplifted the Group members’ poetic stimulation and raised it to a higher, celestial plane. Readers of the Group’s poetry find it clear that religious intertextuality is prominent (Koran, Hadith, religious authorities). For this reason, this study presents a conceptual framework of ‘intertextuality’, in general, in old Arab thought and in non-native, Western thought, regardless of names and translations. The study will also be concerned with clarifying the difference between intertextuality, quotation and summoning, and with explaining the roles of these categories in steering poetic form and enriching its significance. Then a number of the Apollo Group poets will be read in the context of religious intertextuality, where instances (representations) of intertextual quotation and of recollection and summoning, of prominent figures, times, and incidents, whether directly or indirectly, or literally, metaphorically or symbolically, will be examined.